Metabolic Engineering of Bacillus licheniformis for Production of Acetoin - Lü, Chuanjuan; Ge, Yongsheng; Cao, Menghao; Guo, Xiaoting; Liu, Peihai; Gao, Chao; Xu, Ping; Ma, Cuiqing (Frontiers in Bioengineering and Biotechnology, 2020)
Acetoin is a potential platform compound for a variety of chemicals. Bacillus licheniformis MW3, a thermophilic and generally regarded as safe (GRAS) microorganism, can produce 2,3-butanediol with a high concentration, yield and productivity. In this study, B. licheniformis MW3 was metabolic engineered for acetoin production. After deleting two 2,3-butanediol dehydrogenases encoding genes budC and gdh, an engineered strain B. licheniformis MW3 (ΔbudCΔgdh) was constructed. Using fed-batch fermentation of B. licheniformis MW3 (ΔbudCΔgdh), 64.2 g/L acetoin was produced at a productivity of 2.378 g/[L h] and a yield of 0.412 g/g from 156 g/L glucose in 27 h. The fermentation process exhibited rather high productivity and yield of acetoin, indicating that B. licheniformis MW3 (ΔbudCΔgdh) might be a promising acetoin producer.